2019
DOI: 10.1111/vox.12875
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcaemia and traumatic coagulopathy: an observational analysis

Abstract: Background and Objectives Haemorrhage‐associated calcium loss may lead to disruption of platelet function, intrinsic and extrinsic pathway‐mediated haemostasis and cardiac contractility. Among shocked major trauma patients, we aimed to investigate the association between admission hypocalcaemia and adverse outcomes. Materials and Methods Data were extracted from the Alfred Trauma Registry and the Alfred Applications and Knowledge Management Department for all adult major trauma patients presenting directly fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…36,37 Mean ionized calcium concentrations were slightly below the RI but not significantly different between dogs with and without acute traumatic coagulopathy, despite a recent study in people showing an association between ionized hypocalcaemia and the presence of acute traumatic coagulopathy. 38 Several limitations of the study need to be discussed. Some dogs received fluid therapy or opioids prior to the first blood sampling.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Mean ionized calcium concentrations were slightly below the RI but not significantly different between dogs with and without acute traumatic coagulopathy, despite a recent study in people showing an association between ionized hypocalcaemia and the presence of acute traumatic coagulopathy. 38 Several limitations of the study need to be discussed. Some dogs received fluid therapy or opioids prior to the first blood sampling.…”
Section: Discussionmentioning
confidence: 99%
“…7 The importance of calcium in coagulation is supported by studies that demonstrate coagulopathy and increased transfusion requirements in trauma patients who have ionized hypocalcemia on presentation. 8,9 Ionized hypocalcemia also decreases cardiac contractility by limiting calcium release within cardiac myocytes. 10 Furthermore, the hypothermia associated with trauma decreases liver metabolism of citrate and promotes ongoing effects of hypocalcemia.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets rely on calcium for activation and stabilization into a developing thrombus 7 . The importance of calcium in coagulation is supported by studies that demonstrate coagulopathy and increased transfusion requirements in trauma patients who have ionized hypocalcemia on presentation 8, 9 . Ionized hypocalcemia also decreases cardiac contractility by limiting calcium release within cardiac myocytes 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the finding of total blood loss, hip fracture patients with hypocalcemia exhibited a higher blood transfusion rate, although transfusion volume difference did not reach significance. Also, trauma patients [ 22 ], and upper gastrointestinal bleeding patients [ 21 ] with hypocalcemia were most likely to receive a blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Hypocalcemia is a common electrolyte disorder in hospitalized patients, nearly 56.2% in trauma patients [ 18 ]. Many studies have already investigated its harmful effect, and found that hypocalcemia was associated with more bleeding or blood transfusion in patients with intracerebral hemorrhage [ 19 ], postpartum hemorrhage [ 20 ], upper gastrointestinal bleeding [ 21 ], shocked trauma [ 22 ], and total knee arthroplasty [ 23 ].…”
Section: Introductionmentioning
confidence: 99%